Surging bloodstream infections and antimicrobial resistance during the first wave of COVID–19: a study in a large multihospital institution in the Paris region. (January 2022) - Amarsy, Rishma; Trystram, David; Cambau, Emmanuelle; Monteil, Catherine; Fournier, Sandra; Oliary, Juliette; Junot, Helga; Sabatier, Pierre; Porcher, Raphaël; Robert, Jérôme; Jarlier, Vincent; ,; et al.
Highlights: The first wave of COVID-19 in 2020 had collateral bacteriological effects in French hospitals in the Paris region. There was a massive increase in blood culturing. There were higher rates of positive blood culture and of blood stream infection. There was a concomitant increase in antimicrobial resistance (and in antibiotic use). Abstract: Objectives: This study measured the impact of the first wave of COVID-19 pandemic (COVID-19) (March–April 2020) on the incidence of bloodstream infections (BSIs) at Assistance Publique – Hôpitaux de Paris (APHP), the largest multisite public healthcare institution in France. Methods: The number of patient admission blood cultures (BCs) collected, number of positive BCs, and antibiotic resistance and consumption were analysed retrospectively for the first quarter of 2020, and also for the first quarter of 2019 for comparison, in 25 APHP hospitals (ca. 14 000 beds). Results: Up to a fourth of patients admitted in March–April 2020 in these hospitals had COVID-19. The BSI rate per 100 admissions increased overall by 24% in March 2020 and 115% in April 2020, and separately for the major pathogens ( Escherichia coli, Klebsiella pneumoniae, enterococci, Staphylococcus aureus, Pseudomonas aeruginosa, yeasts). A sharp increase in the rate of BSIs caused by microorganisms resistant to third-generation cephalosporins (3GC) was also observed in March–April 2020, particularly in K. pneumoniae, enterobacterial species naturally producing inducible AmpC ( Enterobacter cloacae ...), and P. aeruginosa . A concomitant increase in 3GC consumption occurred. Conclusions: The COVID-19 pandemic had a strong impact on hospital management and also unfavourable effects on severe infections, antimicrobial resistance, and laboratory work diagnostics.